Outcomes Following Reduction of Sanders Type III/IV Calcaneal Fracture Using Impaction Technique and Ligamentous Sparing - Pongsamakthai, MD , Wanjak (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To demonstrate the outcomes of the impacted reduction technique with plating fixation for Sanders type III-IV calcaneal fractures, without detaching the calcaneofibular and talocalcaneal ligaments. Methods: Retrospective analysis of the calcaneal fractures Sanders type III-IV, which were treated with impacted reduction technique and plate fixation during January 2012 to December 2016 was conducted. Medical records and radiographies were reviewed for collecting demographic data and radiographic parameters. Pre-operative and post-operative radiographic parameters were compared. Results: Twenty-seven consecutive calcaneal fractures were evaluated, in which 22 fractures (81.5%) were classified as Sanders type III, underwent the operative treatments at 14.8 days (range, 10-18 days). The impacted reduction technique was able to post-operatively restore the Bohler, Gissane, and varus angles, and the articular stepping from 8.2 (±17.3) to 27.2 (±4.8) degrees, with a mean difference of 19.0 (±17.2) degrees; 99.2 (±14.4) to 126.7 (±7.1) degrees, with a mean difference of 27.6 (±14.1) degrees; 7.3 (±3.6) to 4.4 (±1.1) degrees, with a mean difference of -3.0 (±3.2) degrees; and 4.3 (±0.9) to 0.7 (±0.7) millimeters, with a mean difference of -3.5 (±1.1) millimeters, respectively; with a statistically significant difference (P<0.001). Mean of the estimated blood loss, operative times, and union times were 78.7 milliliters, 99.2 minutes, and 3.5 months, respectively. Conclusion: The impacted reduction technique for Sanders type III-IV calcaneal fractures improved the restoration of the post-operative Bohler angle, Gissane angle, varus malalignment, and articular stepping radiographic parameters. Level of study: Level IV case series.